Characteristics of Student Mental Models in Negative Round Numbers - Tri Febri Marta Lasmana; Mohammad Faizal Amir (Proceedings of The ICECRS, 2020)
The purpose of this study is to know, to describe, and to analyze students' mental model on negative integers. This research uses a descriptive qualitative approach. The data collection techniques use test, observation, interview, and documentation. The data analysis techniques use data reduction, data presentation, and conclusions. The result shows that there are three characteristics of students' metal model, the characteristics of early mental model on negative integers are only able to understand the minus sign as a count operation, students with formal mental model characteristics on negative integers understand the existence of negative numbers that have values ​​smaller than 0 but do not understand that numbers going left on the number line, it can be smaller values. Students with formal mental model characteristics on negative integers understand the direction on the number line and the value of each number correctly. It can be concluded that in understanding the scale of negative integer values ​​and negative integer places on number line, every student has different characteristics. The characteristics of the early mental model are the characteristics of the lowest mental model, the characteristics of the synthesis mental model are the characteristics of the moderate mental model and the characteristics of the formal mental model are the characteristics of the highest mental model in understanding negative integers.